Magnetic stirrer induced dispersive ionic-liquid microextraction for the determination of vanadium in water and food samples prior to graphite furnace atomic absorption spectrometry. (1st April 2015) - Naeemullah,; Kazi, Tasneem Gul; Tuzen, Mustafa
Highlights: Magnetic stirrer induced dispersive ionic-liquid microextraction was developed for trace level of vanadium. 4-(2-Pyridylazo) resorcinol (PAR) was used as complexing agent and analysed by GFAAS. Introduced a novel approach that reduced solvent consumption, effort, time. It was applied for determination of vanadium in water and food samples. Green extraction technique was applied. Abstract: A new dispersive liquid–liquid microextraction, magnetic stirrer induced dispersive ionic-liquid microextraction (MS-IL-DLLME) was developed to quantify the trace level of vanadium in real water and food samples by graphite furnace atomic absorption spectrometry (GFAAS). In this extraction method magnetic stirrer was applied to obtained a dispersive medium of 1-butyl-3-methylimidazolium hexafluorophosphate [C4MIM][PF6] in aqueous solution of (real water samples and digested food samples) to increase phase transfer ratio, which significantly enhance the recovery of vanadium – 4-(2-pyridylazo) resorcinol (PAR) chelate. Variables having vital role on desired microextraction methods were optimised to obtain the maximum recovery of study analyte. Under the optimised experimental variables, enhancement factor (EF) and limit of detection (LOD) were achieved to be 125 and 18 ng L −1, respectively. Validity and accuracy of the desired method was checked by analysis of certified reference materials (SLRS-4 Riverine water and NIST SRM 1515 Apple leaves). The relative standard deviation (RSD) for 10 replicate determinations at 0.5 μg L −1 of vanadium level was found to be <5.0%. This method was successfully applied to real water and acid digested food samples.